Is High Fluoride Toothpaste or Fluoride Mouthwash More Effective in Enhancing Cariostatic Activity among Patients of Orthodontic treatment? - Muhammad Waqas Rashid, Marij Hameed, Athar Parvez, Mamoona Mujtaba, Kanza Nawadat, Sania Saqib (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of current study was to compare the effect of fluoride containing toothpaste and fluoride containing mouthwash during orthodontic treatment. Method: This randomized control trial was conducted in dental hospital of Lahore in the department of orthodontics for 6 months. Sample of 45 patients was taken in the study. Group A received treatment along with regular use of fluoride toothpaste whereas Group B received treatment along with regular use of fluoride mouth wash. Group C received treatment along with regular use of regular toothpaste. Data was entered and analyzed in SPSS version 25. Frequencies and percentages were calculated for gender and mean ± std. deviation was calculated for age. Chi-square test was used to explore the effect of fluoride containing toothpaste and fluoride containing mouthwash during orthodontic treatment Results: The results of chi-square test revealed a significant difference in the effectiveness of fluoride toothpaste, fluoride mouthwash and regular toothpaste in terms of dental caries prevention during orthodontic treatment (X2=17.23, P=.002). Conclusion: Fluoride containing toothpastes are more effective in preventing dental caries among patients undergo orthodontic treatment as compared to fluoride containing mouthwash.